Egg size, weight and fresh egg density of the Scaly-sided Merganser Mergus squamatus in South Primorye, Russia - Solovieva, Diana; Shokhrin, Valery (Wildfowl, 2013)
Egg biometrics data were collected in 2003–2007 in the core breeding area of the Scaly-sided Merganser Mergus squamatus in South Primorye, Russia. Mean egg length was 62.5 mm (s.e. ± 0.1 mm) and mean maximum diameter was 44.7 mm (± 0.1). Data on fresh egg weight and density for the Scaly-sided Merganser are published for the first time; fresh egg weight was 70.7 g (± 0.9) and density was 0.56 g/cc (± 0.002). The mass of a full clutch equates to 76.7% of the female’s body mass before egglaying, and an average Scaly-sided Merganser egg weighs 7.2% of the female’s body mass before egg-laying.